The Impact of Brand Image, Price, and Variety Seeking on Brand Switching Behavior - Firdaus Firdaus; Budiman Budiman (Journal of Advanced Multidisciplinary Research, 2021)
Brand switching behavior is brand switching behavior by consumers or it is interpreted as a consumer's vulnerability to switch to another brand . The purpose of this study to determine the effect of brand image, price and variety seeking to brand switching behavior of the product Slai O'lai with Oreo products. Slai Olai has decreased significantly, whereas it is inversely proportional to Oreo Products which have experienced an increase. This picture shows the changes in consumer behavior makes the transition brand from Slai O'lai of Oreo Product. The population and research sample are residents of Semarang as many as 100 consumers. The sampling technique was carried out using purposive sampling method, namely the sampling technique used by the researcher if the researcher had certain considerations in taking the sample or determining the sample for certain purposes and processing the data using the SPPS version 21 program . The results showed that the fact that the brand shift of biscuit customers was influenced by the brand image, price and the need to look for variations.